Sustainable cities and smart cities: an analysis of Arcadis rankings and European Smart Cities - Flores, Luiz Eduardo Brand (2017)
The present study sought to relate and analyze two city rankings: one of smart cities and other of sustainable cities. For better understanding, concepts of smart cities and sustainable cities were explored and explained. The rankings analyzed by the study were: Arcadis Sustainable Cities Index 2016 for sustainable cities and European Smart Cities for smart cities. Through them, the dimensions and the indicators of each one were described and compared to clarify the similarities and as differences between them. Finally it was noticed that the rankings have similarities, however they diverge in their foci.